To Determine The Frequency Of Vitamin D Deficiency In Patients With Chronic Hepatitis C - Imran Hussain; M. Zill-e-Humayun Mirza; Ali Yusuf (Journal of Bahria University Medical and Dental College)
Objective: To determine the frequency of vitamin D deficiency in patients with chronic hepatitis C (CHC) Design: It was a Descriptive and Cross Sectional study Place and Duration of Study: It was carried out in the Medicine Unit of Pakistan Naval Ship SHIFA, Karachi from Nov 29, 2016 to May 29, 2017. Patients and Methods: Approval was sought from Institutional Review Board before carrying out the study. Proper history, clinical examination and appropriate lab investigations were carried out. Standard techniques were used for blood sample collection. Site used for blood collection was antecubital fossa. Sterile method was used for fasting sample and about 10 ml of blood was collected from each patient. Results: A total of 289 patients were included. Strict exclusion and inclusion criteria was used for study cohort. Mean age (years) of study cohort was 34.51+8.32. There were 188 (65.1) male and 101 (34.9) female patients. Patients with CHC who were vitamin D deficient were 74 (25.6). Conclusion: Patients of CHC had high frequency of vitamin D deficiency which suggests that further studies in the region will be conduct in our general population to know the exact statistics which will pave the way for future researchers